Bile Leak following Laparoscopic Cholecystectomy due to Perforated Duodenal Ulcer in Patient with Roux-en-Y Gastric Bypass - Amanda M. Marsh; Ayman Almousa; Thomas Genuit; David Forcione; Karin Blumofe (Case Reports in Surgery)
Perforated ulcers of the excluded stomach or duodenum are exceedingly rare in patients who have undergone Roux-en-Y gastric bypass surgery. The diagnosis of perforated ulcer after Roux-en-Y gastric bypass remains challenging as there is often absence of free air or contrast extravasation from the biliopancreatic limb. We present a patient with signs and symptoms of acute cholecystitis. Laparoscopic cholecystectomy was complicated by postoperative bile leak. EDGE procedure was performed to access the remnant stomach and endoscopic evaluation revealed a perforated ulcer in the posterior duodenal bulb. Although unusual, in patients with bariatric surgery and upper abdominal pain, differential diagnosis including perforated ulcer of the biliopancreatic limb must be considered and early surgical exploration is essential.